Crowdfunding and risk - David A. Cimon (Bank of Canada, 2023)
This paper examines the role of rewards-based and equity-based crowdfunding in funding new businesses. In this model, crowdfunding is a unique technology that serves as a real option for production and eliminates downside risk. It affords entrepreneurs who face uncertain consumer demand a viable means of funding new projects. Crowdfunding performs well for projects with a high variability in demand and a low probability of success. Conversely, crowdfunding does not perform well for large projects with little variability in demand or for projects where the production side is uncertain.
Keywords: G21; G24; G32; 330; Digital currencies and fintech; Financial markets; Financial services